Utilizing Quality Management Techniques in Minimizing Examination Malpractices at Meru National Polytechnic - Osundwa, Antony; C. Njati, Ibuathu (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Examination culture can shape or taint the image of an institution. Exam malpractices undermine educational integrity, eroding the value of academic qualifications and trust in the education system. Addressing this issue is critical to maintain fairness and uphold standards. This study investigated strategies to minimize exam malpractices through various supervision methods for quality management with a focus on Meru National Polytechnic (MNP) in Kenya. It evaluates the various stages of exam management; exam content setting, handling, packaging, and storage of exam materials, identifying potential vulnerabilities that erode confidence. The study utilized a mixed-methods approach, combining qualitative interviews with educators and quantitative surveys among students to identify vulnerabilities in the exam process. Additionally, a review of existing literature on exam supervision strategies was conducted to evaluate their effectiveness. The findings revealed several key vulnerabilities, including lack of water tight handling procedures, inadequate supervision, inconsistent application of rules, and insufficient training content creators, invigilators and script markers. They indicate a need for enhanced security measures, transparent marking procedures, and effective supervision strategies to mitigate malpractices. Recommendations include strengthening protocols for handling exam materials, standardizing marking practices, and implementing robust invigilation methods. By addressing these concerns, MNP can fortify its assessment processes and ensure fairness for all students. Implementing these recommendations at MNP and similar institutions can enhance the integrity of the examination process providing a roadmap for institutions to improve their examination practices and maintain high standards of academic integrity. Specific steps include mandatory content crerator, invigilator and marking training programs, adoption of surveillance technologies, and a clear communication plan for rules and consequences. These measures will help restore trust in the assessment process and ensure that academic qualifications accurately reflect students’ knowledge and abilities.